Pengembangan Multimedia Interaktif dengan Model Addie Dapat Menumbuhkan Semangat Belajar Peserta Didik Sekolah Dasar - Astuti, Septiana Dwi; Saputri, Desvia; Sari, Indah Maya (Lembaga Yasin AlSys, 2023)
Interactive multimedia is a combination of several types of media that are combined and can be used in propiding explanations related to learning material in the learning process. Many interactive media were created with the goal of creating interactive media so that they can be used in the educational process. In developing interactive multimedia the model used is the ADDIE model (analysis, desaign, development, implementation, and evaluation). In develoving interactive multimedia, the authors chose the ADDIE model because this model is constanty evaluated at each level. When develoving and perfecting a product in interactive multimedia in the form of audio-visual, visual, audio, the ADDIE model can be used. The development of interactive multimedia means that students have high enthusiasm in the learning process.